2016
DOI: 10.1007/s13277-016-5329-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of point mutation P29S in RAC1 on tumorigenesis

Abstract: A point mutation (P29S) in the RAS-related C3 botulinum toxin substrate 1 (RAC1) was considered to be a trigger for melanoma, a form of skin cancer with highest mortality rate. In this study, we have investigated the pathogenic role of P29S based on the conformational behavior of RAC1 protein toward guanosine triphosphate (GTP). Molecular interaction, molecular dynamics trajectory analysis (RMSD, RMSF, Rg, SASA, DSSP, and PCA), and shape analysis of binding pocket were performed to analyze the interaction ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 39 publications
1
73
0
Order By: Relevance
“…It has been shown earlier that the G14V mutant becomes constitutively active since the chemical step of deactivation (GTP hydrolysis) is hindered in this mutant54. Our results for the G14V mutation corroborates the decreased free energy barrier with the increased flexibility in the switch I region as observed in the earlier study36. In addition, the current results indicate that the loop region undergoes a population shift of the conformational states in addition to increased flexibility, which might promote binding to any arbitrary effector proteins through induced fit mechanism.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It has been shown earlier that the G14V mutant becomes constitutively active since the chemical step of deactivation (GTP hydrolysis) is hindered in this mutant54. Our results for the G14V mutation corroborates the decreased free energy barrier with the increased flexibility in the switch I region as observed in the earlier study36. In addition, the current results indicate that the loop region undergoes a population shift of the conformational states in addition to increased flexibility, which might promote binding to any arbitrary effector proteins through induced fit mechanism.…”
Section: Resultssupporting
confidence: 92%
“…However, both the loop regions show significantly lower fluctuations upon nucleotide binding as compared to the nucleotide free state, which signifies the role of these regions in nucleotide binding and/or effector recognition. Earlier simulation studies have shown that mutations in the p-loop or switch regions can significantly alter the degree of flexibility of these regions36373839. A point mutation (P29V) locks the RAC1 in the GTP bound activated state, accompanied by the enhanced flexibility in the SWI region and rigidity in the SWII region36.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been widely used to study the effect of single or multiple mutations. For example, it was applied to several proteins such as l-alanine dehydrogenase [28], protein tyrosine phosphatase 1B [29], HIV-1 RT [30] and RAS-relate C3 botulinum toxin substrate 1(RAC1) [31]. Therefore, MD simulations have been used for extensive analysis, and the results often help to explain the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Hence, the molecular simulation approaches could be considered as a significant strategy for investigating the effect of gramicidin peptides undoubtedly. Recently, molecular dynamics (MD) focused with much attention on the mutational effects in drug targets, their resistance mechanism, drug binding effects on targeted protein etc.…”
mentioning
confidence: 99%